Dysfunction of soluble guanylyl cyclase in aorta and kidney of Goto-Kakizaki rats: influence of age and diabetic state - Witte, Klaus; Jacke, Kerstin; Stahrenberg, Raoul; Arlt, Gerrit; Reitenbach-Blindt, Ina; Schilling, Lothar; Lemmer, Björn (Nitric oxide, 2002)
Type 2 diabetes mellitus is frequently associated with arterial hypertension. The mechanisms involved in this association are not known in detail, but endothelial dysfunction and a blunted vascular response to endogenous vasodilators are thought to play a role. In the present study we investigated the in vitro activity of vascular and renal soluble guanylyl cyclase in type 2 diabetic Goto-Kakizaki rats aged 5, 15, and 30 weeks, in comparison with age-matched Wistar controls. Blood pressure was monitored by radiotelemetry, and serum glucose and insulin concentrations were measured by standard assays. Goto-Kakizaki rats of all age groups had serum glucose concentrations significantly higher than those of corresponding Wistar controls. Serum insulin was unchanged until 15 weeks of age and was elevated in the 30-week-old diabetic rats. Blood pressure in Goto-Kakizaki rats was significantly higher than that in Wistar controls, and heart rate was significantly lower. Mesenteric arteries of diabetic rats showed a blunted relaxation in response to acetylcholine and sodium nitroprusside. In aortic tissue from Wistar rats an age-dependent increase was found in nitric oxide-stimulated cGMP formation, which was absent in the diabetic animals. Moreover, the maximum activity of soluble guanylyl cyclase was significantly lower in Goto-Kakizaki rats in all age groups studied. In renal tissue no differences were found between diabetic and control rats, except at 30 weeks of age when Goto-Kakizaki rats showed a significant reduction in basal and stimulated guanylyl cyclase activity. In conclusion, the present study shows a persistent reduction in vascular nitric oxide-sensitive guanylyl cyclase in Goto-Kakizaki rats, which occurred shortly after weaning and may contribute to the elevation in blood pressure in this strain of genetically diabetic rats.
Published online July 20, 2001
Gesehen am 07.04.2022